Nairobi City County Food System Profile - Lamba, Davinder; Omondi, Samuel (CGIAR System Organization, 2024)
Agrifood systems have been identified as a critical component in the search for solutions to the challenges that face humanity’s transition to an urban world. Growing pollution and environmental degradation, increasing social and economic inequalities, growing competition for land and water resources, and weak or absent agrifood governance structures are some of the key challenges. Research action on the urban and peri-urban (UPU) agrifood systems could generate change that can secure food and livelihoods for future urban generations. The possibility prompted the Resilient Cities through Sustainable Urban and Peri-urban Agrifood Systems Initiative (Resilient Cities) to stimulate new approach to research on the urban agrifood sectors. Nairobi City County Food System Profile is the outcome of the research activity undertaken by Mazingira Institute as part of the global initiative of addressing the challenges facing the agrifood systems in urban settings. The overall research initiative, titled Resilient Cities Through Sustainable Urban and Peri-urban Agrifood Systems (Resilient Cities), is by CGIAR Centres and partners. Its geographic scope is global, with priority activities in Bangladesh, Philippines, Kenya, Ethiopia, Ghana, and Peru. RUAF, a global partnership on sustainable agriculture and food systems and a partner in Resilient Cities, is contributing to implementation of Work Package Five, ‘Strengthening research and innovation capacity’. RUAF operates as a consortium of partners that includes Mazingira Institute, a Kenyan civil society organisation; hence, the latter is implementing the Nairobi activities of the work package as a partner of RUAF